SPE Annual Technical Conference and Exhibition 2009
DOI: 10.2118/125095-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure, Temperature, and Solution Gas on Oil Recovery From Surfactant Polymer Floods

Abstract: Surfactant-polymer (SP) and alkali-surfactant-polymer (ASP) flooding is of great current interest owing to the need to recover oil left behind after primary and secondary recovery. If designed properly, these enhanced oil recovery processes can give very high oil recoveries. Microemulsion phase behavior plays a central role in process performance and is typically measured by doing salinity scans in glass pipettes at atmospheric pressure and reservoir temperature using dead crude oil from the reservoir of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…,Roshanfekr et al (2009), Southwick et al (2012,Sagi et al (2013) andJang et al (2014).Jang et al (2014) used sapphire cells to measure the phase behavior for eight different oil samples over a wide range of pressure, temperature and solution gas and is the most complete set of data available at this time Roshanfekr et al (2009), Southwick et al (2012. andJang et al (…”
mentioning
confidence: 99%
“…,Roshanfekr et al (2009), Southwick et al (2012,Sagi et al (2013) andJang et al (2014).Jang et al (2014) used sapphire cells to measure the phase behavior for eight different oil samples over a wide range of pressure, temperature and solution gas and is the most complete set of data available at this time Roshanfekr et al (2009), Southwick et al (2012. andJang et al (…”
mentioning
confidence: 99%
“…Therefore and despite the volatility of oil prices, it is fair to conclude that operators and surfactant manufacturers are showing a growing interest in EOR chemical flooding [132,133]. This trend is also noticed with an increase of screening and lab studies to evaluate or re-estimate EOR potential of chemical flooding in different basins [134][135][136][137][138][139][140][141].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Nelson (1983), Puerto and Reed (1983), Austad and Strand (1996), Roschanfekr et al (2009) andSoutwick et al (2010) showed experimentally that dissolving methane increases the surfactant relative solubility with oil and then decresases the optimal salinity. The impact of pressure on phase diagram has been studied by Skauge and Fotland (1990), Kahlweit et al (1988), Austad et al (1990), Sassen et al (1991), Austad and Strand (1996) and Roschanfekr et al (2009) who observed that an increase in pressure shifts the optimal salinity to higher salinities. Few models are presented to explain surfactant phase behavior with crude oil, pressure and dissolved gas.…”
Section: Introductionmentioning
confidence: 99%